Next generation touch interface - Teh, Zhi Wei. (2013)
With the proliferation of touch-enabled devices in the form of mobile devices, like smart phones and tablets, and personal computers, there is increasingly more research in touch screen technology. One area of research is to find a low-cost yet scalable